Elephant space use in relation to ephemeral surface water availability in the eastern Okavango Panhandle, Botswana - Makati, Anastacia (Department of Environmental and Geographical Science, 2023)
The movement and distribution of elephants can be influenced by environmental factors over time (Foley, 2002). Examining how features in the landscape such as vegetation productivity, water sources and anthropogenic activities drive the movement of elephants can help in understanding patterns of movement. It can also help to inform the establishment and alignment of protected areas, wildlife corridors and identification of tourism hotspots as well as policy interventions to manage Human-Elephant Conflict (HEC). The Okavango Panhandle in Botswana is a HEC hotspot and the focus of My study. A number of strategies to address HEC are underway in the area, however one longer term strategy that has been proposed in this area involves provision of artificial water sources to influence elephant movements and keep animals away from fields during the cropping season. However, an improved understanding of how elephants utilize their habitats in relation to natural ephemeral surface water and other factors that influence their movements from dryland habitats to the Okavango Delta resources is needed to inform such management decisions. My study seeks to establish the role of ephemeral surface water on elephant distribution in the eastern Okavango Panhandle, Botswana as well as assess the movement distribution of elephants in relation to the seasonality, proximity and spatial extent of water presence represented by ephemeral surface water. Time series analysis of water extent on ephemeral surface water of the eastern Okavango panhandle will be developed and overlaid with elephant movement datasets. Elephant collar data from 15 elephants (5 males and 10 females) in the eastern Okavango Panhandle, Botswana have been analysed and Home Range (HR) sizes estimated using Kernel Density Estimation (KDE). The relative importance/probability of environmental variables in determining elephants' movement based on the Utilization Distribution (UD) were computed using Generalized Linear Mixed Models (GLMMs). I utilized a remote sensing spectral index, namely the Automated Water Extraction Index (AWEI) to delineate ephemeral surface water in dryland (excluding permanent waters) of the study area. The results reveal that during the wet season, elephants were evenly spread out all over the study area until the early dry season (April-June) when the ephemeral waterholes dried up. Elephants moved southwards towards the permanent waters of the Okavango River, where there are many human settlements and farms. Male HR sizes were found to be bigger than those of female elephants. Wet season (early and late) home range sizes were also bigger when compared to dry season (early and late) HR size. Mean daily distances were computed to investigate the effect of season on elephant daily distances and the distances ranged between 5km and 6.8km in the late wet and in the early wet and late dry season respectively. The Resource Selection Function (RSF) analysis shows that water adjacent sites are preferred over distant ones and both sexes prefer areas with high NDVI, with this preference being more pronounced in males. The seasonal variation of water use is notable in that it affirms the importance of proximity to water for elephants and has implications for their management and HEC. For example, I found that ephemeral surface water has a significant role in influencing elephant spatial use in the area, particularly during the early and late wet season. As ephemeral pans dried and NDVI (vegetation greenness) decreased, elephants started to move closer to the Okavango Delta and consequently human settlements and fields. However, further investigations into the timing of movements away from ephemeral waterholes and the influence of other environmental factors on elephant movements in the area would be needed before any recommendations can be made regarding artificial water provision in this area.